External user’s complaints in a national reference pediatric center - Shimabuku, Roberto (2014)
Objective: To identify complaints characteristics of external users in a national pediatric reference center. Design: Descriptive, retrospective study. Setting: Instituto Nacional de Salud del Niño (INSN), Lima, Peru. Material: Book of Complaints. Methods: A database was elaborated from the INSN Book of Complaints for the period July 2011 to September 2012. The patient could have had more than one complaint reason. Main outcome measures: Demographic data, frequency, motives, time of resolution, alluded personnel, and solution of complaints. Results: Two hundred and eighty-three formats were collected containing 358 complaints. Most frequent complaint reasons were: inappropriate attitude 32.1%, long waiting time 18.4%, deficient information 14.5%, deficient access to services 9.5%, loss of documentation (laboratory results or x-rays, formats, clinical records, among others) 7.8%, problems in communication 7.5%, privileged access to attention 5.9%, objective aspects (facilities, appearance, cleaning, equipment) 4.2%. The areas that received more complaints were: outpatient attention by physicians 41.7% (rate of 0.5 per thousand patients), security 9.2%, private hospital service 9.2%, and cashiers 6.0%. Sixty per cent of claims were solved, and of these 84.2% were solved before 4 weeks since the complaint. Occupational groups generating complaints were: physician (26,4%), nurse technician (13,9%), administrative personnel (12,2 %), security personnel (12,2%), archive personnel (9,7 %), nurse (9,0 %), cashier (5,9 %), admission (2,1%). Conclusions: Complaints’ characteristics suggest the need to take appropriate corrective and educational measures, so as to avoid or decrease them. Routine periodic evaluation of complaints is necessary to increase user’s satisfaction.